One‐Step Process for Press Hardened Steel–Carbon Fiber Reinforced Thermoset Polymer Hybrid Parts - David Penney (Steel Research International, 2020)
A new one‐step process for manufacturing press hardened steel–carbon fiber reinforced (thermoset) polymer hybrid parts with potential for reduced cycle time, infrastructure requirements, and energy consumption compared with traditional two‐ and three‐step processes is developed. The process combines and optimizes the press hardening and prepreg compression molding technologies, traditionally used in isolation for manufacturing press hardened steel and carbon fiber reinforced polymer parts, respectively, to produce hybrid parts in a one‐step, fully integrated process. Heat required for curing and bonding prepreg to steel is provided by residual heat of the steel part immediately following hot forming and interrupted die‐quenching of steel. Thermal conductivity of tool material is investigated to achieve the optimal balance between die‐quenching rate for martensite formation in steel and temperature maintenance for complete curing and bonding of prepreg. Addition of epoxy adhesive and thickness ratio between steel and prepreg are also investigated. Benchmarking is conducted against parts manufactured by the traditional two‐step process, in which the press hardened steel part is formed in isolation before joining with the carbon fiber reinforced polymer part. No sacrifice of part quality is found from the new one‐step process with no loss of mechanical performance, despite clear economic and environmental advantages.